2004
DOI: 10.1021/je0342567
|View full text |Cite
|
Sign up to set email alerts
|

Solubilities of Alkylcyclohexanes in Water from 30 °C to 180 °C

Abstract: A solid-phase extraction method has been developed for measuring low solubilities of hydrocarbons in water. The solubilities in water of methylcyclohexane, ethylcyclohexane, trans-1,2-dimethylcyclohexane, and a mixture of 1,2-dimethylcyclohexane isomers (respectively, 89.3 mol % and 10.7 mol % of the cis and trans isomers) were determined at temperatures ranging from (30 to 180)°C. At 30°C, the mole fraction solubility is (2.96 ( 0.03) × 10 -6 for methylcyclohexane, (0.699 ( 0.007) × 10 -6 for ethylcyclohexane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 6 publications
1
17
0
Order By: Relevance
“…Thus by fitting the parameters in Eq. (12) to the solute solubility database, we concluded that an adequate model is: for the whole database, which demonstrate the ability of Eq. (13) to predict the solubility in water from 298 to 573 K of 34 solutes of widely differing chemical characteristics (Table 1) to within one order of magnitude.…”
Section: Data Correlationmentioning
confidence: 57%
See 1 more Smart Citation
“…Thus by fitting the parameters in Eq. (12) to the solute solubility database, we concluded that an adequate model is: for the whole database, which demonstrate the ability of Eq. (13) to predict the solubility in water from 298 to 573 K of 34 solutes of widely differing chemical characteristics (Table 1) to within one order of magnitude.…”
Section: Data Correlationmentioning
confidence: 57%
“…Solute solubility database and data correction Table 1 summarizes the solutes and solubility data sources [4][5][6][7][8][9][10][11][12][13][14] that were considered to derive an alternative correlation to Eq. (1) for the effect of system temperature on solute solubility [5] in liquid water, at the tabulated temperature and pressure ranges, and the units used to report the solute's solubility in water.…”
Section: Methodsmentioning
confidence: 99%
“…The equations reproduce the constants to within 0.02 log units over the Table 6. For four cyclohexanes, we combined the solubilities determined by Marche et al [24] with vapor pressures from the equations given by Stevenson and Malinowski [25].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it captures well the minimum 99 Ng et al, 100 and Economou et al 101 (d) Cyclohexane/water. Experimental data by Burd et al, 102 Guseva et al, 103 Pereda et al, 104 Marche et al, 92 Pierotti et al, 105 Goldman et al, 106 and Tsonopoulos et al 90 (e) Benzene/water. Experimental data by Tsonopoulos et al 90 (f) p-Xylene/water.…”
Section: Industrial and Engineering Chemistry Researchmentioning
confidence: 99%